Affecting Factors of Shooting Ability In Basketball Games: Coordination And Concentration - Rachmat Hidayat; Suaib Nur; M. Iqbal Hasanuddin; Besse Baso W (JUARA : Jurnal Olahraga, 2023)
The shooting technique is a movement in which a player shoots the ball towards the opposing team's basketball ring. In shooting, it is necessary to have optimal physical conditions and psychological aspects. Eye-hand coordination and concentration as support to perform a series of movements when shooting. This study aims to determine the coordination and concentration shooting in basketball games for physical education students at the University of Muhammadiyah Palopo. The sample is 29 students who take class A1 basketball courses in semester 3. The results show that the correlation between hand-eye coordination and shooting ability had a significant relation of 0.000>0.05. The correlation between concentration with shooting ability is significant at 0.000>0.05. It can be concluded that coordination and concentration are strongly related to basketball shooting ability